Book review: Porter, G., Hampshire, K., Abane, A., Munthali, A., Robson, E. and Mashiri, M., editors, 2017: Young People's Daily Mobilities in Sub-Saharan Africa, Moving Young Lives. (July 2018) - Philip, Shannon
Porter, G., Hampshire, K., Abane, A., Munthali, A., Robson, E. and Mashiri, M., editors, 2017: Young People's Daily Mobilities in Sub-Saharan Africa, Moving Young Lives . New York, NY: Palgrave Macmillan. XVII + 250 pp. £92.00 (Hardcover). ISBN: 9781137454317.